Preparation method of boron-potassium nitrate composite energetic material

Through the combination of ultrasonic method and organic solvent, the problems of long time and large energy consumption during the coating process of boron-based composite energy-containing materials are solved, and high-efficiency and low-energy-consuming coating are achieved, and the specific surface area and heat release performance of the material are improved. , improves combustion efficiency and ignition performance.

CN119306554APending Publication Date: 2025-01-14NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411365302.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing preparation methods of boron-based composite energy-containing materials have problems such as long cladding time, large energy consumption, and uneven cladding layer, which leads to high ignition temperature and low heat release, which affects its application.

Method used

The ultrasonic method is used to mix potassium nitrate with boron-based material, add organic solvent for stirring and drying at normal temperature and pressure. The difference in solubility of potassium nitrate and organic solvents can quickly crystallize and precipitate, shorten the coating time and reduce the Energy consumption and improve coating uniformity.

Benefits of technology

The simplification and safety of the coating process are achieved, the reaction time is shortened, energy consumption is reduced, the specific surface area and heat release performance of the potassium nitrate-coated boron-based material is improved, the ignition temperature is reduced, and the combustion efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306554A_ABST
    Figure CN119306554A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a boryl-potassium nitrate composite energetic material, which comprises the following steps: mixing potassium nitrate with water according to a solid-to-liquid ratio of 1: (2-5) to obtain a potassium nitrate solution; adding a boron-based material accounting for 30% of the mass of potassium nitrate into the potassium nitrate solution, adding a dispersant accounting for 3% of the volume of the potassium nitrate solution, and carrying out ultrasonic treatment at 20-60 DEG C for 0.5-2 hours to obtain a mixed suspension; placing the mixed suspension on a stirring table, adding an organic solvent which is 1-8 times of the volume of the mixed suspension at the stirring speed of 300r / min-600r / min, stirring and reacting for 10s-60s, then carrying out suction filtration, and drying for 2-5h at the temperature of 30-80 DEG C, so as to obtain the composite energetic material of the potassium nitrate coated boron-based material. The stirring reaction process does not need to be heated and can be completed at normal temperature and normal pressure, the reaction time is short, the energy consumption is low, the operation is simple, and the potassium nitrate coated magnesium boride composite energetic material prepared by the method disclosed by the invention has the advantages of larger specific surface area, higher heat release and lower ignition temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an energetic material, and in particular to a method for preparing a boron-potassium nitrate composite energetic material. Background Art

[0002] The study of the ignition characteristics of energetic materials is of great significance for solving practical problems related to explosion safety assessment and transient process calculations in various applications, including rocket and space technology, weapons, and pyrotechnics; these energetic particles can generate a large amount of heat when reacting, which is essential for any device that produces energy or thrust. Many of these energetic particles may help to improve combustion efficiency and reduce exhaust emissions; in recent decades, boron (B) has stood out due to its high volumetric calorific value (136.44kJ / cm3) and mass calorific value (58.30MJ / kg) and clean combustion products; therefore, boron-based composite energetic materials have been widely studied and used in solid rocket propellants, explosives, and pyrotechnics.

[0003] At present, the preparation methods of boron-based composite energetic materials mainly include the following methods:

[0004] Wet chemical method: first, disperse boron powder or boride in an aqueous solution according to a certain solid-liquid ratio to prepare a dispersed slurry of boron or boride, and then add a certain amount of potassium nitrate according to the coating ratio. Since potassium nitrate has a large solubility in aqueous solution, it will quickly dissolve in the dispersed slurry, and then the aqueous solution is evaporated by heating and evaporation. The potassium nitrate dissolved in the water crystallizes due to the evaporation of the solution, thereby forming a potassium nitrate surface coating layer on the surface of the boron or boron compound.

[0005] Spray drying method: firstly, boron or boride and potassium nitrate are dispersed in an aqueous solution according to a certain solid-liquid ratio to prepare a suspension solution, and then the suspension solution is dispersed into fine droplets by an atomizer and introduced into hot air. Under the heating of hot air, it is quickly evaporated and dried into dry powder. Potassium nitrate crystallizes and deposits on the surface of boron or boride due to the evaporation of the solution.

[0006] High-energy ball milling method: High-energy ball milling method is to mechanically mix boron or boride with potassium nitrate in a certain ratio. The powder is subjected to collision, impact, shearing and extrusion under the repeated impact of the grinding ball medium, and is constantly deformed, fractured and welded. High-intensity and long-term grinding makes the powder fully uniform and refined, and finally becomes a composite energetic material of boron or boride and potassium nitrate with dispersed reinforcement.

[0007] Electrostatic spray method: Step (1): prepare a boron powder precursor solution and a potassium nitrate precursor solution respectively; Step (2): use the precursor solution prepared in step (1) as the raw material, adopt a coaxial electrostatic spray device, pass the boron powder precursor solution into the inner layer of the coaxial needle, and pass the potassium nitrate precursor solution into the outer layer, the two solutions converge at the front end of the coaxial needle, and move toward the conductive substrate under the action of the electric field. During the spraying process, the solvent evaporates, and the potassium nitrate precipitates and coats the surface of the inner layer boron particles to form a core-shell structure of boron / potassium nitrate, which is received by the conductive substrate.

[0008] However, the above preparation method has problems such as long coating time, high energy consumption, and uneven coating layer. In addition, the uneven coating layer will also lead to high ignition temperature and low heat release of boron-based composite energetic materials, which will lead to ignition difficulties, low combustion efficiency, and incomplete calorific value release, affecting its application. Summary of the invention

[0009] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a boron-based-potassium nitrate composite energetic material.

[0010] The present invention is achieved by the following technical solutions:

[0011] A method for preparing a boron-based-potassium nitrate composite energetic material comprises the following steps:

[0012] Mix potassium nitrate and water in a solid-liquid ratio of 1:2-5 to obtain a potassium nitrate solution;

[0013] Adding a boron-based material of 30% by mass of potassium nitrate to a potassium nitrate solution and a dispersant of 3% by volume of the potassium nitrate solution, and ultrasonicating for 0.5-2h at 20-60°C to obtain a mixed suspension, wherein the boron-based material comprises one of boron and a boride or a mixture thereof;

[0014] At room temperature, the mixed suspension is placed on a stirring table, and an organic solvent of 1 to 8 times the volume of the mixed suspension is added at a stirring rate of 300 r / min-600 r / min. The mixture is stirred for reaction for 10 s to 60 s, and then filtered and dried at 30° C. to 80° C. for 2 to 5 h to obtain a composite energetic material of potassium nitrate-coated boron-based material.

[0015] Furthermore, the boride is magnesium boride.

[0016] Further, the following steps are included:

[0017] Mix potassium nitrate and water in a solid-liquid ratio of 1:3 to obtain a potassium nitrate solution;

[0018] Add magnesium boride (30% by mass of potassium nitrate) and dispersant (3% by volume of potassium nitrate solution) to the potassium nitrate solution, and ultrasonicate at 60° C. for 1 h to obtain a mixed suspension;

[0019] At room temperature, the mixed suspension was placed on a stirring table, and an organic solvent twice the volume of the mixed suspension was added at a stirring rate of 600 r / min. The mixture was stirred for 30 seconds, and then filtered and dried at 60°C for 4 hours to obtain a composite energetic material of potassium nitrate coated magnesium boride.

[0020] Furthermore, the dispersant includes but is not limited to polyethylene glycol 200, polyethylene glycol 400, polyethylene glycol 600 or a mixture of several thereof.

[0021] Furthermore, the organic solvent includes but is not limited to anhydrous methanol, propanol, propylene glycol, acetone or a mixture of several thereof.

[0022] The beneficial effects of the present invention are:

[0023] 1. The preparation method of the present invention has a simple process. The coating process adopts an anti-solvent precipitation method. The solubility of potassium nitrate in water and in an organic solvent is greatly different, so that potassium nitrate is rapidly crystallized during the addition of an organic solution. The stirring reaction does not require heating and can be completed at room temperature and pressure. The reaction time is short, the energy consumption is low, the operation is simple, the coating reaction is convenient and safe, and large-scale production is possible.

[0024] 2. The preparation method of the present invention can shorten the contact distance between magnesium boride particles and potassium nitrate particles, and improve the combustion performance and combustion efficiency of boron through the magnesium element of magnesium boride and the potassium nitrate coated on the surface.

[0025] 3. Compared with Comparative Example 1, the composite energetic material of potassium nitrate coated with magnesium boride prepared by the present invention has a larger specific surface area, higher heat release, and lower ignition temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope image of magnesium boride raw material;

[0027] Figure 2 This is a scanning electron microscope image of the MgB2@KNO3 composite energetic material prepared in Example 1;

[0028] Figure 3 DSC graphs of the MgB2 / KNO3 composite energetic material prepared in Comparative Example 1 and the MgB2@KNO3 composite energetic material prepared in Example 1;

[0029] Figure 4 Infrared thermal imaging images of the ignition reactions of the MgB2 / KNO3 composite energetic material prepared in Comparative Example 1 and the MgB2@KNO3 composite energetic material prepared in Example 1. DETAILED DESCRIPTION

[0030] The above contents of the present invention are further described in detail below with reference to specific implementation modes. However, the protection scope of the present invention is not limited to the implementation modes of the present invention.

[0031] The application of boron-based materials faces the following three challenges: (1) The protective oxide layer on the surface of boron powder gradually thickens during combustion, resulting in poor ignition performance and long ignition time delay; (2) The low melting point (718K) and high boiling point (2316K) of B2O3 cause a liquid film to form on the surface of boron particles during combustion, hindering the diffusion of oxygen and reducing the combustion efficiency of boron (the melting point and boiling point of pure boron are 2500K); (3) Impurities such as B2O3 and H3BO3 can react with the hydroxyl groups of hydroxy-terminated polybutadiene (HTPB) to form a gel layer on the surface of boron powder, resulting in poor compatibility between boron and HTPB.

[0032] At present, the method of coating boron-based materials with potassium nitrate is time-consuming. Due to the serious self-nucleation during the crystallization of potassium nitrate, it is easy to cause uneven coating layer on the surface of boron-based materials, poor product uniformity, small specific surface area, insufficient contact with air during combustion, resulting in high ignition temperature, high surface activation energy, and low heat release.

[0033] Embodiment 1:

[0034] The boron-based material of this embodiment uses magnesium boride, and the preparation method is as follows: potassium nitrate is mixed with water in a solid-liquid ratio of 1:3 to obtain a potassium nitrate solution; magnesium boride in an amount of 30% by mass of potassium nitrate and polyethylene glycol 600 in an amount of 3% by volume of the potassium nitrate solution are added to the potassium nitrate solution, and ultrasonicated at 60° C. for 1 h to obtain a mixed suspension; at room temperature, the mixed suspension is placed on a stirring table, and at a stirring rate of 600 r / min, anhydrous methanol in an amount twice the volume of the mixed suspension is added, and the mixture is stirred for reaction for 30 seconds, followed by suction filtration and drying at 60° C. for 4 hours.

[0035] Example 2: The preparation method is as follows: potassium nitrate is mixed with water in a solid-liquid ratio of 1:5 to obtain a potassium nitrate solution; magnesium boride in an amount of 30% by mass of potassium nitrate and polyethylene glycol 600 in an amount of 3% by volume of the potassium nitrate solution are added to the potassium nitrate solution, and ultrasonicated at 30°C for 2 hours to obtain a mixed suspension; at room temperature, the mixed suspension is placed on a stirring table, and at a stirring rate of 600 r / min, anhydrous methanol in an amount of 2 times the volume of the mixed suspension is added, the mixture is stirred for reaction for 20 seconds, and then filtered and dried at 60°C for 4 hours.

[0036] Example 3: The preparation method is as follows: potassium nitrate is mixed with water in a solid-liquid ratio of 1:2 to obtain a potassium nitrate solution; magnesium boride in an amount of 30% by mass of potassium nitrate and polyethylene glycol 400 in an amount of 3% by volume of the potassium nitrate solution are added to the potassium nitrate solution, and ultrasonicated at 30°C for 0.5h to obtain a mixed suspension; at room temperature, the mixed suspension is placed on a stirring table, and at a stirring rate of 300r / min, anhydrous methanol in an amount of 1 times the volume of the mixed suspension is added, the reaction is stirred for 10s, and then filtered and dried at 30°C for 2h.

[0037] Example 4: The preparation method is as follows: potassium nitrate is mixed with water in a solid-liquid ratio of 1:4 to obtain a potassium nitrate solution; magnesium boride in an amount of 30% by mass of potassium nitrate and polyethylene glycol 400 in an amount of 3% by volume of the potassium nitrate solution are added to the potassium nitrate solution, and the mixture is ultrasonicated at 50°C for 1 hour to obtain a mixed suspension; at room temperature, the mixed suspension is placed on a stirring table, and at a stirring rate of 500 r / min, anhydrous methanol in an amount of 3 times the volume of the mixed suspension is added, the mixture is stirred for reaction for 40 seconds, and then the mixture is filtered and dried at 60°C for 3 hours.

[0038] Example 5: The preparation method is as follows: potassium nitrate is mixed with water in a solid-liquid ratio of 1:3 to obtain a potassium nitrate solution; magnesium boride in an amount of 30% by mass of potassium nitrate and polyethylene glycol 600 in an amount of 3% by volume of the potassium nitrate solution are added to the potassium nitrate solution, and the mixture is ultrasonicated at 50°C for 1.5 hours to obtain a mixed suspension; at room temperature, the mixed suspension is placed on a stirring table, and at a stirring rate of 500 r / min, anhydrous methanol in an amount of 4 times the volume of the mixed suspension is added, the mixture is stirred for reaction for 60 seconds, and then the mixture is filtered and dried at 50°C for 2 hours.

[0039] Example 6: The preparation method is as follows: potassium nitrate is mixed with water in a solid-liquid ratio of 1:3 to obtain a potassium nitrate solution; magnesium boride in an amount of 30% by mass of potassium nitrate and polyethylene glycol 600 in an amount of 3% by volume of the potassium nitrate solution are added to the potassium nitrate solution, and the mixture is ultrasonicated at 50°C for 1 hour to obtain a mixed suspension; at room temperature, the mixed suspension is placed on a stirring table, and at a stirring rate of 300 r / min, anhydrous methanol in an amount of 2 times the volume of the mixed suspension is added, the mixture is stirred for reaction for 30 seconds, and then the mixture is filtered and dried at 50°C for 2 hours.

[0040] Comparative Example 1: MgB2 / KNO3 composite energetic material prepared by the prior art high energy ball milling method.

[0041] Comparative Example 2: The difference compared with Example 1 is that potassium nitrate is mixed with water in a solid-to-liquid ratio of 1:6.

[0042] Comparative Example 3: The difference compared with Example 1 is that potassium nitrate is mixed with water in a solid-to-liquid ratio of 1:8.

[0043] Comparative Example 4: The difference compared with Example 1 is: ultrasonication at 65°C for 1h.

[0044] Comparative Example 5: The difference compared with Example 1 is that anhydrous methanol is added in an amount 9 times the volume of the mixed suspension.

[0045] Comparative Example 6: The difference compared with Example 1 is: the reaction is stirred for 8 seconds.

[0046] Comparative Example 7: The difference compared with Example 1 is: stirring reaction for 9s

[0047] Comparative Example 8: The difference compared with Example 1 is: the reaction is stirred for 65 seconds.

[0048] Specific surface area experiment:

[0049] The experimental instrument used was Micromeritics ASAP 2460 instrument.

[0050] The experimental process is as follows:

[0051] Clean the measuring surface of the Micromeritics ASAP 2460 tester to ensure the accuracy of the measurement results; plug the tester into the power outlet and wait for the tester to start up. After the instrument starts up, place the sample on the tester's measuring surface and make sure it has good contact with the surface. Press the measurement button on the tester and the tester will start measuring the surface area of ​​the object being measured. After the measurement is completed, record the measurement results automatically displayed by the tester.

[0052] Heat release experiment:

[0053] The experimental instrument used was METTLER TOLEDO TGA / DSC 3+ instrument.

[0054] The experimental process is as follows:

[0055] Open the gas cylinder valve of the TGA / DSC 3+ instrument, adjust the pressure of the secondary pressure gauge to less than 0.2MPa, turn on the balance protection gas (high-purity argon), adjust the flow rate to 20ml / min, turn on the power of the constant temperature water bath, set the temperature to 20℃, turn on the power of the TGA / DSC 3+ host after half an hour, set the instrument heating rate to 15K / min, and the test temperature range to 50℃-800℃, then put the test sample into the instrument, start the test after the instrument is stable, and record the experimental results after the test.

[0056] The comparison of specific surface area and heat release is shown in Table 1:

[0057] Table 1. Comparison of specific surface area and heat release

[0058] sample <![CDATA[Specific surface area (m2 / g)]]> Heat release (J / g) Example 1 8.4312 1772 Example 2 7.6824 1614 Example 3 6.5342 1373 Example 4 7.9571 1672 Example 5 8.1946 1722 Example 6 8.3621 1757 Comparative Example 1 1.6294 1233 Comparative Example 2 5.6635 1190 Comparative Example 3 4.5922 965 Comparative Example 4 7.6583 1309 Comparative Example 5 4.6592 979 Comparative Example 6 5.6325 1183 Comparative Example 7 6.7342 1365 Comparative Example 8 7.8533 1650

[0059] From Table 1 we can see that:

[0060] The solid-liquid ratio of potassium nitrate to water has a great influence on the heat release of the obtained composite material. When the solid-liquid ratio of Comparative Examples 2 and 3 exceeds 6 times, the heat release is significantly reduced. The too high solid-liquid ratio results in a low potassium nitrate concentration due to the large amount of solution. When methanol is added for anti-solvent precipitation, the self-nucleation will be greater than the heterogeneous nucleation, resulting in a large amount of potassium nitrate self-nucleating and precipitating and cannot be coated on the magnesium boride, resulting in a low specific surface area of ​​the prepared composite material.

[0061] In Comparative Example 4, the excessively high ultrasonic temperature has a negative impact on the heat release of the prepared composite material.

[0062] In Comparative Example 5, excessive anhydrous methanol will cause a large solution volume, thereby resulting in poor heat release of the composite material obtained by coating.

[0063] The stirring reaction time has a great influence on the material preparation effect, especially when the reaction time is insufficient, the heat release is greatly reduced. The materials prepared in Comparative Examples 6 and 7 with stirring reaction time less than 10s have small specific surface areas, while the stirring reaction time in Comparative Example 8 exceeding 60s cannot continuously increase the specific surface area of ​​the prepared material, but instead leads to a decrease in the specific surface area. This phenomenon may be attributed to the rapid change in the solution environment in a short period of time. This change causes a significant difference in the solubility of potassium nitrate in the two solutions, thereby inducing the precipitation of potassium nitrate, which helps to form a larger specific surface area. However, as time goes on, the dissolution of potassium nitrate in the two solutions reaches a certain equilibrium state, and part of the potassium nitrate dissolves in each solution, which is not conducive to a further increase in the specific surface area.

[0064] like Figure 3 The DSC graphs of the MgB2 / KNO3 composite energetic material prepared in Comparative Example 1 and the MgB2@KNO3 composite energetic material prepared in Example 1 are shown; Figure 3 It can be seen that under the same test conditions, the MgB2@KNO3 formed by coating with this technology has a higher heat flow peak and an earlier reaction temperature, which is of great significance in the field of energetic materials, indicating that the energetic materials prepared by this technology have higher reaction activity and better heat release efficiency.

[0065] like Figure 4 The infrared thermal imaging images of the ignition combustion of the MgB2 / KNO3 composite energetic material prepared in Comparative Example 1 and the MgB2@KNO3 composite energetic material prepared in Example 1 are shown; Figure 4It can be seen that under the same test conditions, the MgB2@KNO3 energetic material formed by coating with this technology has a larger flame and a higher temperature when burning, which indicates that the energetic material prepared by this technology has higher reactivity and better energy release efficiency.

Claims

1. A method for preparing a boron-based-potassium nitrate composite energetic material, characterized in that: The following steps are involved: Mix potassium nitrate with water in a solid-liquid ratio of 1:2-5 to obtain a potassium nitrate solution; Adding a boron-based material in an amount of 30% by mass of potassium nitrate and a dispersant in an amount of 3% by volume of the potassium nitrate solution to a potassium nitrate solution, and ultrasonicating for 0.5-2h at 20-60°C to obtain a mixed suspension, wherein the boron-based material comprises one of boron and a boride or a mixture thereof; At room temperature, the mixed suspension is placed on a stirring table, and an organic solvent of 1 to 8 times the volume of the mixed suspension is added at a stirring rate of 300 r / min-600 r / min. The mixture is stirred for reaction for 10 s to 60 s, and then filtered and dried at 30° C. to 80° C. for 2 to 5 h to obtain a composite energetic material of potassium nitrate-coated boron-based material.

2. The preparation method according to claim 1, characterized in that: The boride is magnesium boride.

3. The preparation method according to claim 1, characterized in that: The following steps are involved: Mix potassium nitrate and water in a solid-liquid ratio of 1:3 to obtain a potassium nitrate solution; Add magnesium boride (30% by mass of potassium nitrate) and dispersant (3% by volume of potassium nitrate solution) to the potassium nitrate solution, and ultrasonicate at 60°C for 1 hour to obtain a mixed suspension; At room temperature, the mixed suspension was placed on a stirring table, and an organic solvent twice the volume of the mixed suspension was added at a stirring rate of 600 r / min. The mixture was stirred for 30 seconds, and then filtered and dried at 60°C for 4 hours to obtain a composite energetic material of potassium nitrate coated magnesium boride.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The dispersant includes, but is not limited to, polyethylene glycol 200, polyethylene glycol 400, polyethylene glycol 600, or a mixture of the two or more thereof.

5. The preparation method according to any one of claims 1 to 3, characterized in that: The organic solvent includes, but is not limited to, anhydrous methanol, propanol, propylene glycol, acetone, or a mixture of the two or more thereof.